Investimentos das empresas brasileiras de saneamento básico e indicadores de eficiência - Alves, Ana Carolina Menezes (2023)
This study aimed to investigate the relationship between investments made by basic sanitation companies in Brazil and their efficiency indicators. The study is based on the aspect of public policies brought by the Theory of Public Choices (TEP) and delimits the analysis to basic sanitation and water supply services (SAA). This is a quantitative research and to achieve the objective, 2,348 Brazilian municipalities were analyzed, with 11,740 observations, through the application of the statistical technique of regression with panel data, using 2 (two) financial (FN), as dependent variables, dealing specifically with investments made and total collection. For each of the dependent variables, a research hypothesis was developed and 10 (ten) financial and operational indicators were used to measure efficiency. It should be noted that all information and indicators used were extracted from the historical series of the National Sanitation System (SNIS) data platform, from 2016 to 2020. Subsidiarily, an analysis of the legal nature of basic sanitation companies in the country, developing (H3) in order to verify the correlation with the level of investments and efficiency indicators of these. Furthermore, for the purpose of analyzing the indicators, considering that the norm of the National Water and Basic Sanitation Agency (ANASB) that will deal with efficiency standards in Brazil has not yet entered into force, the standards of the SNIS average. From the obtained results, it was verified that both dependent variables obtained significant results. Inferring that investments made by basic sanitation companies in Brazil can affect efficiency indicators, as (4) four significant results were obtained among the 10 (ten) independent variables analyzed. The collection of basic sanitation companies in Brazil is also related to the results of their efficiency indicators, since at least 7 (seven) of the 10 (ten) independent variables obtained significant results and, therefore, is related to the efficiency indicators. In this way, both investments (H1) and collection (H2) partially affect the efficiency indicators of the country's sanitation companies, that is, the public policies adopted in the SAA, due to the discretionary capacity of Governments, can improve or harm efficiency, taking political decisions to the detriment of the true public interest. With regard to (H3) it was possible to identify that, in 97.3% of the municipalities in the sample, the SAA is managed by public companies. Thus, the low representation of private companies was not relevant in view of the identified results. In view of the findings, it is expected that the research will contribute to the literature, by proposing an analysis of financial and operational data from sanitation companies, in addition to verifying the importance of the TEP in public administration, and in the scope of public accounting, since it is about of an area with extensive exploitation . Thus, it is also expected that this study will contribute to the enhancement of the development of public policies, by the competent authorities, based on the discretion of the Governments brought by the TEP, and mainly in relation to the sanitation services of the SAA